Enhanced biofuel production potential with nutritional stress amelioration through optimization of carbon source and light intensity in Scenedesmus sp. CCNM 1077. (March 2015) - Pancha, Imran; Chokshi, Kaumeel; Mishra, Sandhya
Graphical abstract: Highlights: Scenedesmus sp. utilizes various carbon sources under mixotrophic growth. Combination of glucose and high light intensity enhances biofuel capabilities. 70% carbohydrate was obtained in nitrogen stress condition under mixotrophic growth. Mixotrophic growth condition significantly ameliorates nutritional stress. Scenedesmus sp. is a potential feed stock for biodiesel and bio-ethanol production. Abstract: Microalgal mixotrophic cultivation is one of the most potential ways to enhance biomass and biofuel production. In the present study, first of all ability of microalgae Scenedesmus sp. CCNM 1077 to utilize various carbon sources under mixotrophic growth condition was evaluated followed by optimization of glucose concentration and light intensity to obtain higher biomass, lipid and carbohydrate contents. Under optimized condition i.e. 4 g/L glucose and 150 μmol m −2 s −1 light intensity, Scenedesmus sp. CCNM 1077 produced 1.2 g/L dry cell weight containing 23.62% total lipid and 42.68% carbohydrate. Addition of glucose shown nutritional stress ameliorating effects and around 70% carbohydrate and 25% total lipid content was found with only 21% reduction in dry cell weight under nitrogen starved condition. This study shows potential application of mixotrophically grown Scenedesmus sp. CCNM 1077 for bioethanol and biodiesel production feed stock.